2019
DOI: 10.1155/2019/5782974
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hazards Associated with Raw Donkey Milk Consumption: A Review

Abstract: Donkey milk can be used as a substitute for infants and children who suffer from cow milk proteins intolerance and multiple food hypersensitivity. Up to date, this is one of the main reasons why donkey milk has become a substantial area for reasearch, with an increase over the the last fifteen years. In donkey milk chain, risk analysis should be the object of particular attention because children are the main consumers of this food. In fact, this process is one of the main tool to achieve a high level of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 64 publications
(95 reference statements)
0
26
0
7
Order By: Relevance
“…Also, donkey milk is characterized by a low somatic cell count, with an average value around 35 × 1000 mL −1 [ 47 , 48 , 49 ]. As to the total bacterial count, the literature data indicate values ranging from 7 cfu mL −1 to 90,000 cfu mL −1 , both for horse and donkey milk ( Table 2 ), and it is generally considered that they do not frequently harbor foodborne pathogens due to antimicrobial properties connected to substances such as lactoferrrin, lysozyme, immunoglobulins, and lactoperoxidase [ 34 , 50 , 51 , 52 , 53 , 54 ]. However, hygienic issues have sometimes been reported [ 53 ].…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, donkey milk is characterized by a low somatic cell count, with an average value around 35 × 1000 mL −1 [ 47 , 48 , 49 ]. As to the total bacterial count, the literature data indicate values ranging from 7 cfu mL −1 to 90,000 cfu mL −1 , both for horse and donkey milk ( Table 2 ), and it is generally considered that they do not frequently harbor foodborne pathogens due to antimicrobial properties connected to substances such as lactoferrrin, lysozyme, immunoglobulins, and lactoperoxidase [ 34 , 50 , 51 , 52 , 53 , 54 ]. However, hygienic issues have sometimes been reported [ 53 ].…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…As to the total bacterial count, the literature data indicate values ranging from 7 cfu mL −1 to 90,000 cfu mL −1 , both for horse and donkey milk ( Table 2 ), and it is generally considered that they do not frequently harbor foodborne pathogens due to antimicrobial properties connected to substances such as lactoferrrin, lysozyme, immunoglobulins, and lactoperoxidase [ 34 , 50 , 51 , 52 , 53 , 54 ]. However, hygienic issues have sometimes been reported [ 53 ]. For example, Zhang et al [ 51 ] reported that even though Salmonella choleraesuis and Shigella dysenteriae showed a certain sensitivity to natural antimicrobial compounds in donkey milk, the growth of most micoorganisms was not affected by them.…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…Conte and Panebianco [9] provide a comprehensive background of the potential hazards associated with raw donkey milk consumption, suggesting the need to enhance the current scientific knowledge, to allow a suitable risk assessment along the whole donkey milk chain. Moreover, the authors solicited competent authorities to carry out more stringent official controls, with particular attention given to the level of primary production, as well as improving the traceability system in the donkey milk chain.…”
Section: Analysis Of Bacterial Diversitymentioning
confidence: 99%
“…Due to its physico-chemical composition and nutritional quality similar to human milk, donkey milk is mainly used for feeding infants who suffer from a cows' milk protein allergy, or immunocompromised elderly people [7,8]. However, due to the small production and target market of the consumers, potential safety hazards, including the bacterial quality of raw donkey milk, should be subjected to stricter regulation [9]. Indeed, due to its high nutritional content, milk can support a rich microbiota, including beneficial, spoilage, and pathogenic microorganisms [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest for donkey milk production and commercialization due to its similar composition with human milk, making it ideal for consumption by sensitive population groups such as infants with cow milk protein allergy (CMPA), the immunocompromised, and the elderly [ 1 ]. According to the literature, raw donkey milk has a low total bacterial count; nevertheless, the presence of foodborne pathogens such as E. coli 0157 , S. aureus , Campylobacter spp., and Cronobacter sakazaki was also detected [ 2 , 3 , 4 , 5 ]. Therefore, raw donkey milk is subjected to thermal pasteurization in order to ensure its microbiological safety and to comply with the European Community Regulation 853/2004.…”
Section: Introductionmentioning
confidence: 99%